Comments on two sides of CEO pay injustice: A power law conceptualization of CEO over and underpayment. (9th April 2018) - Conyon, Martin J.
Abstract : Purpose: This is a short commentary on Herman Aguinis, Geoffrey Martin, Luis Gomez-Mejia, Ernest Boyle and Harry Joo (2017): "Two sides of CEO pay injustice: A power law conceptualization of CEO over and underpayment." Design/methodology/approach: Using insights from prior studies on executive compensation, the author's commentary presents a critical evaluation of "Two sides of CEO pay injustice: […]." In addition, the author offers potential avenues for further research. Findings: The paper "Two sides of CEO pay injustice" is well executed and makes several significant contributions to the management and executive compensation literature. Particularly, noteworthy are the use of advanced quantitative methods, the use of power law distributions to explain chief executive officer (CEO) pay outcomes, the focus on pay-for-performance and the role of justice in CEO outcomes. The author's commentary in the present paper discusses the measurement of CEO pay and performance, poses alternative estimation methods to explore the pay-for-performance link and offers thoughts on justice theory in the context of CEO pay. Research limitations/implications: The authors' findings may be briefly stated as CEO pay is better described by a power law distribution than a normal distribution, CEO pay is not linked to firm performance and the patterns of CEO pay does not conform to patterns of distributive justice. Overall, the authors provide an important way to evaluate CEO pay outcomes. Thy set the stage for new avenues of research. Practical implications: CEO pay is a highly controversial subject in the domain of corporate governance. This paper offers boards of directors and policymakers a method to better understand the success or failure of boardroom pay policies. Social implications: CEO pay is an important social measure. Originality/value: The authors' paper is original by offering a method for determining over and underpayment of CEOs. The author in the present paper makes suggestions on how one might extend the research. Abstract : Objetivo – Este es un comentario sobre el trabajo de Herman Aguinis, Geoffrey Martin, Luis Gomez-Mejia, Ernest Boyle y Harry Joo (2017): "Two sides of CEO pay injustice: A power law conceptualization of CEO over and underpayment". Diseño/metodología/aproximación – Utilizando las ideas de la literatura previa sobre retribución de ejecutivos, mi comentario presenta una evaluación crítica del artículo "Two sides of CEO pay injustice: […]". Además, esbozo algunas ideas para la investigación futura. Resultados – El artículo "Dos lados de la injusticia de la retribución de los CEO" está bien desarrollado y realiza varias contribuciones significativas a las literaturas de gestión y retribución de ejecutivos. En particular, son de señalar: a) el uso de métodos cuantitativos avanzados, b) el uso de la distribución de ley de poder para explicar los resultados de la retribución de los CEO, c) el foco en el pago por resultados, d) el papel de la justicia en el rendimiento del CEO. Mi comentario a) discute las medidas de retribución y rendimiento del CEO, b) propone métodos de estimación alternativos para la relación entre retribución y rendimiento y c) ofrece ideas en torno a la teoría de la justicia en el contexto de la retribución del CEO. Implicaciones – Los resultados de los autores pueden resumirse así: a) La retribución de los CEO se describe mejor como una distribución de ley de poder que como una distribución normal, b) la retribución del CEO y el rendimiento empresarial no están conectados, c) los patrones de retribución del CEO no concuerdan con los patrones de justicia distributiva. En general, los autores proporcionan un importante método para evaluar los resultados de la retribución de los CEO y fomentar la investigación futura. Implicaciones prácticas – La retribución del CEO es un tema muy controvertido en el ámbito del gobierno corporativo. Este artículo proporciona a los consejos de administración y a los decisores públicos un método para entender mejor el éxito o fracaso de las prácticas retributivas en los consejos de administración. Originalidad/valor – El trabajo de los autores es original al ofrecer un método para determinar la sobre o la infra retribución de los CEO. Yo apunto algunas sugerencias sobre cómo puede extenderse esta investigación. Abstract : Objetivo – Este é um breve comentário a Herman Aguinis, Geoffrey Martin, Luis Gomez-Mejia, Ernest Boyle and Harry Joo (2017): "Two sides of CEO pay injustice: A power law conceptualization of CEO over and underpayment". Metodologia – Usando conhecimentos de estudos anteriores em compensação executiva, o meu comentário apresenta uma avaliação crítica de "Two sides of CEO pay injustice:….". Adicionalmente, ofereço potenciais avenidas para investigação futura. Resultados – O artigo "Two sides of CEO pay injustice" está bem feito e apresenta diversas contribuições importantes à literature sobre compensação executiva e de gestores. Em particular, são de salientar: a) o uso de métodos quantitativos avançados b) o uso de distribuições da lei de potência para explicar os resultados do pagamento a CEOs c) O enfoque no pagamento pela performance d) o papel da justiça nos resultados para o CEO. O meu comentário a) discute a medida de pagamento ao CEO e do desempenho b) Propõe métodos alternativos de estimação para explorar a ligação pagamento ao desempenho e c) Apresenta argumentos da teoria da justiça no contexto da compensação do CEO. Implicações – Os resultados dos autores podem resumir-se como: a) Compensação do CEO é mais bem descrita por uma distribuição da lei de potência que por uma distribuição normal b) Compensação do CEO não está ligada à performance da empresa c) Os padrões da compensação do CEO não se conformam com justiça distributiva. Em geral, os autores fornecem uma forma importante de avaliar a compensação do CEO. Apresentam por isso novas vias para investigação futura. Implicações práticas – Compensação do CEO é um tópico controverso do domínio da governança corporativa. Este artigo oferece aos Conselhos de Administração e decisores politicos um método para melhor perceber o sucesso ou insucesso das políticas de pagamento aos membros das Administrações. Originalidade/valor – O artigo é original e oferece um método para determinar sobre ou sub compensação do CEO. Faço sugestões de como se pode estender a investigação.